Comparative study on biophysical ecosystem service mapping methods—a test case of carbon stocks in Finnish Forest Lapland. (February 2017) - Mononen, Laura; Vihervaara, Petteri; Repo, Teppo; Korhonen, Kari T.; Ihalainen, Antti; Kumpula, Timo
Highlights: Evaluate applicability of two data sources and two methods using carbon as an example. Carbon storage assessment was done by using two different sources of data and differences were found. The use for habitat data was found useful despite the fact that modelled method show variation across landscape. The most sophisticated, complex and detailed data and methods are not necessarily better, but their usability depends on the question addressed. Abstract: Mapping of ecosystem services in biophysical environment helps distinguishing the nature's benefits in our surroundings. Ecosystem services also enable assessing the level of sustainability of the use of the environment. Various methods are being used for mapping them and methods: vary from expert evaluations to complex modelling. All methods: are related with uncertainties and affect to their applicability for different purposes. In this study, two different level biophysical mapping based datasets were tested; 1) data combination of biophysical polygon GIS data (SutiGIS) and statistics, and 2) modelled data of National Forest Inventory were evaluated to compare the differences between the methods: for carbon storages. Our results show that there are differences between results that have been produced in different levels of complexity. However, we also discovered that simpler datasets can also help detecting the shortcomings that may occur in modelling. We discuss also the potential applications of the used datasets in terms of providing information on biodiversity in ES assessments.